Using Your Handheld Lawn and Garden Sprayer - Frederick M. Fishel (EDIS)
PI-175, a 4-page illustrated fact sheet by F. M. Fishel, advises homeowners in choosing the right type of handheld sprayer and using it properly. Includes examples and additional sources of information. Published by the UF Department of Agronomy, January 2009.